1996
DOI: 10.3109/03005369609078424
|View full text |Cite
|
Sign up to set email alerts
|

Audiological findings after multichannel cochlear implantation in patients with Mondini dysplasia

Abstract: Mondini dysplasia is a congenital malformation of the inner ear. To date, five individuals with this malformation have received cochlear implants at the South of England Cochlear Implant Centre. The aim of this study was to review the audiological findings of these individuals after implantation. The soundfield thresholds after implantation are in the region of 30-40 dB (A). The results of suprathreshold speech recognition tasks show substantial variability in performance but this is no greater than that obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Previous studies have already shown that cochlear implantation in such cases is possible [1][2][3][10][11][12][13][14][15][16][17][18][19]. However, the diagnosis of the precise malformation of the cochlea is essential, as factors such as selection of electrode type, programming of surgical approach and high risk of cerebrospinal fluid gushing have to be clarified before any intervention [1][2][3].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have already shown that cochlear implantation in such cases is possible [1][2][3][10][11][12][13][14][15][16][17][18][19]. However, the diagnosis of the precise malformation of the cochlea is essential, as factors such as selection of electrode type, programming of surgical approach and high risk of cerebrospinal fluid gushing have to be clarified before any intervention [1][2][3].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies also suggested cochlear implantation for malformed cases. However, they either used other classifications examining all IP patients under the same group [1,11,[13][14][15]19] or referred to small cohorts or even case reports [3,12,16,18]. Thus, the precise outcome and benefits of the patients in cases of IP-I could not be shown.…”
Section: Cochlear Implantation In Ipmentioning
confidence: 89%
See 1 more Smart Citation
“…Various authors have reported improvement of auditory perception in several patients with inner ear malformation after cochlear implantation [2,[9][10][11]. In contrast, other authors report that patients with severe inner ear malformation are not suitable candidates for cochlear implantation as there may be an increased risk of accidental penetration of the electrode array through the fundus in the internal auditory canal [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although inner ear malformation was once regarded as a contraindication for cochlear implantation [8], studies at different centers [10][11][12][13][14][15][16][17] have proved this treatment not only to be feasible surgically, but also to be beneficial for the children from an audiological point of view.…”
Section: Introductionmentioning
confidence: 99%